Determination of Diethyl Amine by Stop Flow Technique - Dakhil Nassir Taha (Journal of Global Pharma Technology, 2020)
The aim of this research is determination of diethyl amine by stop flow injection analysis technique. The method is based on the reaction between diethyl amine with NQS reagent. This method involves a homemade new valve, which is manufactured from a cheap available material. Optimization of the conditions of the reaction includes, flow rate, sample volume, reagent volume, reagent concentration and reaction coil length were done. Linearity was in the range of (1-10 v/v %), correlation coefficient (R2) was 0.9967. The method was applied successfully to the determination of diethyl amine in aqueous solution. Keywords: Diethyl amine, FIA, Stop flow technique, Dispersion.